Implementation of Simple Additive Weighting and Rank Order Centroid in Determining Field Work Practices - Syabrina Bunga Virella; Zulfaa Aprilia Faiqoh; Achmad Sidik; R. Didik Heriyantoro (Komunitas Dosen Indonesia, 2025)
The development of information technology plays a major role in supporting the decision-making process, one of which is through the development of a Decision Support System (DSS). DSS is needed in the world of education, especially in Vocational High Schools, which prioritize the development of vocational skills to prepare students for the world of work. One of the important programs in Vocational High School is Field Work Practice, which provides students with direct work experience in industry. However, the placement process of Field Work Practice students at Wipama Vocational High School is still done manually without the support of a structured system, so there is often a mismatch between student competencies and industry needs. To overcome these problems, this research develops a DSS by combining the Rank Order Centroid (ROC) and Simple Additive Weighting (SAW) methods. ROC serves to determine the weights of five selection criteria, namely interview scores, vocational practices, academic scores, attitudes, and discipline. While the SAW method serves to calculate the value of student preferences based on these weights. This research was conducted on 10 students from the Light Vehicle Engineering (TKR) major. The results show that the system makes the selection process more efficient and selective than the manual method, and is able to recommend Field Work Practice placement in accordance with student competencies. It is hoped that this system can be an effective solution in supporting student placements.